Regulasi Emosi Ibu Bekerja Dan Kuliah Dalam Pengasuhan Anak Usia Dini - Ulfah, Fitria; Tresna, Elis Hidayah (LP2M STAI Al-Musaddadiyah Garut, 2025)
Mothers with dual roles or with the term working mother and also in college generally have greater responsibilities compared to mothers who do not work. Therefore, the chances of working and studying mothers to feel tired both physically and emotionally will be much greater. This research was conducted with the aim of finding out how emotional regulation in mothers works and also lectures where there is a conflict between work outside the home, college assignments and household work conflicts, namely caring for early childhood and factors that affect emotional regulation This research uses a qualitative method with a case study design. Participants in this study were selected based on a purposive approach with certain criteria, namely working mothers, studying at STAI AL-Musaddadiyah Garut and also having early childhood. Data collection was carried out by interviewing participants and then the data was processed. The results showed that the participants were able to bring up aspects of emotion regulation, including aspects of situation selection, situation modification, attention deployment, cognitive change and response modulation. And factors in the regulation of emotions include gender, age and environment. Keywords: Emotion Regulation, Working Mothers, Early Childhood Parenting.